Efficacy of Adenosine in the Differential Diagnosis of Narrow QRS Complex Tachyarrhythmia: A Case Diagnosed with Atrial Flutter After Adenosine - Aziz Zeytin; Çapan Konca; Celal Varan (Journal of Pediatric Emergency and Intensive Care Medicine)

(untitled)
The most common tachyarrhythmias in childhood are narrow QRS complex tachyarrhythmias. The majority of these are supraventricular tachycardia (SVT). If electrocardiography is inconsistent with typical SVT, another underlying arrhythmia should be considered. In this case, a patient with narrow complex tachycardia who was diagnosed with atrial flutter after adenosine was presented to increase awareness on the subject.